Extra-axial Cerebellopontine Angle Adult Medulloblastoma: An Unusual Presentation at an Unusual Site - Ratha, Vishwaraj; Karmarkar, Vikram S.; Deopujari, Chandrashekhar E. (Indian Journal of Neurosurgery, 2019)
Medulloblastoma is a rare adult primary brain tumor and its presence in the cerebellopontine angle (CPA) constitutes an even rarer site for origin. There are only 40 reported cases of CPA medulloblastoma in the literature, with most being intra-axial and occurring in the pediatric population. Extra-axial CPA medulloblastoma in adults are extremely rare and only 10 adult cases have been reported in world literature.We report a rare case of primary extra-axial CPA medulloblastoma occurring in an adult. We review the literature for such an unusual presentation of medulloblastoma in adults and discuss its appropriate clinico-radiological features along with its possible pathogenesis and surgical management.With increasing reporting of such tumors, CPA region, medulloblastoma should be considered a differential diagnosis of intra-axial or extra-axial CPA tumor, as their further management and prognosis differ significantly. Adjuvant radiotherapy and combined chemotherapy regimen should be added to the postoperative management.
Keywords: cerebellopontine angle medulloblastoma; extra-axial; differential diagnosis; adult